Health education practices of poisoning prevention for child in Family Health Strategy - Camila Cristiane Formaggi Sales; Magda Lúcia Félix de Oliveira (Universidade Federal do Rio de Janeiro, 2019)
Abstract Objective: To analyze health education practices developed by health professionals of the Family Health Strategy team in the context of childhood poisoning. Method: Qualitative research, carried out during the months of July and August 2016, with 50 health professionals from nine Family Health Strategy teams of the city of Maringá-Paraná. Data were collected through semi-structured interviews and, subsequently, submitted to the thematic content analyses. Results: There were different perceptions and living experiences among uniprofessional or multi-professional members of the team. Those were built by different professional categories that were working with families developing prevention activities about childhood poisoning. Those activities in groups of health education were intended to bring health professionals closer to the Users, through dialogue. Conclusion: Indeed, health education practices were based on the concept of first aids, and adopting a biomedical perspective. A little discussed of poisoning accident prevention during childhood showed that those practices were away from a dialogical health education.